DGI-Indonesia.com: Empat Tahun untuk Komuniti Indonesia Kreatif - Danu Widhyatmoko (Bina Nusantara University, 2011)
DGI-Indonesia.com as a community site is able to answer the new needs of the virtual space. This paper will begin with the history of DGI-Indonesia.com; then the discussion about the roles undertaken by the DGI-Indonesia.com. Research method used in this paper is literature study, continued with reflective data analysis. By the end of the paper, a more comprehensive picture about DGI-Indonesia.com's activities such as a forum for self-actualization, interaction, exploration that helps sustain the development of science-based and creative professions in Indonesia.